Relationship between financial literacy and financial distress among youths in Malaysia - an empirical study - Faoziah Haji Idris,; K. Sarojani Devi Krishnan,; Norfiza Azmi, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
This paper examines the relationship between the levels of financial literacy and financial distress among Malaysian youths. A quantitative approach was adopted to determine the relationship between variables of financial literacy and those of financial distress. Questionnaires from previous studies were used to determine the levels of financial literacy and financial distress of 430 youths. The findings show that the levels of respondents’ financial distress and financial literacy were moderate. The study also shows that there is a positive but weak relationship between financial literacy and level of financial distress. The implications of the study points to the fact that the organizations concerned would do well to invest in human resources, in particular, with respect to personal financial management for their employees as such knowledge investment would help raise the level of financial literacy among employees and achieve the organisations’ own objectives of high productivity. This is evidenced in previous studies that indicated that financial distress was one of the factors leading to reduced productivity at the workplace. As such this investment in reducing the employees’financial distress by way of enhancing their financial literacy would serve, in the long run, to improve the effectiveness of the country’s delivery system, especially in the public service.